A study on Scalable and Secure Intrusion Detection in Network Security - Arifa, Shaik; Kesavulureddy, E (International Journal of Computer Sciences and Engineering, 2025)
Wireless Sensor Network (WSN) has a gigantic scope of uses, for example, front line, reconnaissance, crisis protect activity and savvy home innovation and so forth. Aside from its intrinsic requirements, for example, restricted memory and vitality assets, when sent in threatening ecological conditions, the sensor hubs are powerless against physical catch and other security limitations. These limitations put security as a noteworthy test for the analysts in the field of PC organizing. This paper reflects different issues and difficulties identified with security of WSN, its security engineering. The paper likewise gives an exchange on different security instruments conveyed in WSN condition to beat its security dangers.